Insignificant Effect of Isolated Hypothyroxinemia on Pregnancy Outcomes During the First and Second Trimester of Pregnancy - Chen, Liangmiao; Yang, Hong; Ye, Enling; Lin, Zhenzhen; Peng, Mengmeng; Lin, Hai; Yu, Lechu; Cai, Zhuhua; Lu, Xuemian (Frontiers in Endocrinology, 2020)
Objective: Adverse maternal outcomes and perinatal complications are associated with overt and subclinical maternal hypothyroidism. It is not clear whether these complications also occur in women with isolated hypothyroxinemia during pregnancy. The aim of this study was to evaluate the effects of isolated hypothyroxinemia on maternal and perinatal outcomes during pregnancy. Methods: This study included data from 2,864 pregnant women in the first trimester (67 women with isolated hypothyroxinemia, 784 euthyroid women) and the second trimester (70 women with isolated hypothyroxinemia, 1,943 euthyroid women) of pregnancy. Maternal serum samples were collected in the first and second trimesters to examine thyroid hormone concentration. Hypothyroxinemia was defined as a normal maternal thyroid-stimulating hormone concentration with a low maternal free thyroxine concentration and negative thyroid autoantibodies. The following maternal outcomes were recorded: gestational hypertension, gestational diabetes mellitus, placenta previa, placental abruption, prelabor rupture of membranes, and premature delivery. Perinatal outcomes, including fetal growth restriction, fetal distress, low birth weight, intrauterine fetal death, and malformation. The incidence of adverse pregnancy outcomes and perinatal complications was compared between women in the first trimester and second trimester with isolated hypothyroxinemia. Results: There were no significant differences in the incidence rates of adverse maternal outcomes and perinatal complications between patients in the first and second trimesters with isolated hypothyroxinemia. Conclusion: The results of this study indicate that isolated hypothyroidism does not increase the incidence of adverse maternal outcomes and perinatal complications.